Factors influencing adverse event and error reporting in anaesthesiology - Nel, Steven Robert (My University, 2017)
Background Adverse events and errors are a widespread cause of morbidity and mortality in the health care environment. Adverse event and error reporting systems have been shown to potentially reduce the occurrence of these events, however there is still significant underreporting. Little is known regarding the barriers to reporting of adverse events and errors in the context of South Africa, or what emotional and attitudinal barriers may be present regarding a formal reporting system amongst anaesthetists in the Department of Anaesthesiology at the University of the Witwatersrand. Methods A prospective, descriptive, contextual study design utilizing an anonymous self-administered questionnaire was distributed to 133 anaesthetists who attended academic anaesthetic meetings. Results One hundred and eighteen questionnaires met the criteria for analysis, giving a response rate of 92%. Barriers to reporting included a “code of silence” in medicine and blame from colleagues. If a specified error as opposed to an adverse event had occurred, participants were more likely to agree with barriers regarding fear of litigation, disciplinary action, getting into trouble, as well as colleagues that may be unsupportive. Strategies to promote reporting of adverse events and errors include senior role models who encourage reporting and individualised feedback regarding reports made. Conclusions Most anaesthetists in our study disagreed with barriers to reporting an unspecified adverse event. However, if an error has occurred, reporting behaviour may be inhibited by barriers regarding fears of litigation, disciplinary action and lack of support. Senior role models that openly support reporting along with individualised feedback may increase reporting rates.
A research report submitted to the faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Medicine in Anaesthesiology Johannesburg, 2017
Keywords: Anesthesiology Adverse Event (AE)